Camera-based close-range coordinate metrology - Sims-Waterhouse, Danny (2020)
The main focus of this thesis was on the development of techniques and methodologies to allow the effective application of photogrammetry to coordinate metrology. The current understanding of the propagation of uncertainty through camera-based measurement systems is limited due to the highly complex and non-linear nature of the techniques. Additionally, the application of existing verification standards is unclear and difficult to apply directly to high-accuracy photogrammetry systems. The aim of this work was, therefore, to develop techniques to evaluate the coordinate measurement uncertainty of photogrammetry systems as well methods that allow existing verification standards to be effectively applied.